STUDENTS’ STUDENTS’ CRITICAL THINKING AND PROBLEM-SOLVING SKILLS IN SOCIAL STUDIES LESSON CONTENT IN ELEMENTARY SCHOOL - Siti Faridah, Ida (International Conference on Elementary Education, 2024)
Critical thinking and problem-solving skills are skills needed in the challenges of 21st century skills in the era of the Industrial Revolution 4.0 and as competencies that must be possessed by students. The research conducted aims to determine the real conditions in elementary schools in improving students’ critical thinking and problem-solving skills in social studies learning. This research was conducted using qualitative descriptive research methods that aimed to find out and explore how teacher strategies in designing social studies learning in the classroom. While the data collection techniques carried out by researchers in preliminary studies are interviews, observations and documentation. The results of this study explain that the implementation of learning is carried out using lecture, question and answer and discussion methods, the learning model has not varied tends to be monotonous as a way to improve critical thinking and problem-solving skills but not in accordance with the correct steps